2016
DOI: 10.1021/acs.jafc.6b02184
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Microemulsions of Myricetin for Improving Its Antiproliferative and Antioxidative Activities and Oral Bioavailability

Abstract: To improve the bioactivity and oral bioavailability of myricetin, a microemulsion formulation was successfully developed, which consisted of Cremophor RH40 (12%), Tween 80 (6%), Transcutol HP (9%), WL 1349 (18%), and distilled water (55%). With lower content of surfactants and higher stability after dilution and storage for 6 months, the optimized myricetin microemulsion (MYR-ME) could dramatically enhance the solubility of myricetin 1225 times that in water. MYR-ME significantly increased antiproliferative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The entrapment efficiency was measured by the HPLC method described in the previous study (Guo et al., 2016). In short, an HS15-Myr micelle solution was filtered with a 0.22 μm filter; then 100 μl of the filtrate was dissolved and diluted by the appropriate amount of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The entrapment efficiency was measured by the HPLC method described in the previous study (Guo et al., 2016). In short, an HS15-Myr micelle solution was filtered with a 0.22 μm filter; then 100 μl of the filtrate was dissolved and diluted by the appropriate amount of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…Having a longer alcohol molecule, Transcutol can increase the rate of transport from the dermis layer in comparison to alcohol. These attribute to select Transcutol for the preparation of SQR-loaded SNEDDs 48Figure 1Solubility of SQR in various oils, surfactants, and cosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…Blood collection was performed as per the protocol, and serum SQR concentrations were used to calculate the pharmacokinetic parameters. An earlier reported HPLC method was used to determine the plasma SQR concentrations 48. The mobile phase in the system used was methanol/0.05M potassium dihydrogen orthophosphate buffer (pH 5.0; 85/15 v/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myricetin is stable at pH 2 and its degradation depends on pH and temperature [91]. A recent study showed that microemulsion formulation can improve the solubility of myricetin 1225 times greater than water and also enhance its anti-proliferative activity against human liver cancer cells (HepG2) [92]. Myricetin is a promising anti-carcinogen and chemo preventive agent with therapeutic potential reported in ovarian [93], colon [94], skin [95], liver [96] and breast [97] cancers.…”
Section: Myricetinmentioning
confidence: 99%